Effect of Pseudomonas fluorescens different strains on germination and seedling growth of two barley cultivars - سید محمد رضا احتشامی; محیل پور ابراهیمی (علوم و فناوری بذر ایران)
In order to investigate the effect of Pseudomonas different strains on germination and seedling growth of two barley cultivars (Fasih and Bahman), an experiment was conducted as factorial based on a completely randomized design with three replicationsin laboratory of Agriculture College of University of Guilan. In this experiment, barley seeds of Fasih’s and Bahman’s cultivars inoculated with strains 93103, 36, 93103, 9336, 36103, 9310336. No inoculation treatment considered as control. Investigated characteristics were included radicle wet weight, plumule wet weight, radicle dry weight, shoot dry weight, radicle and shoot length, germination percentage, germination speed, vigor index and seedling water percentage. Obtained results showed that bacterium effect was significant on all of indices, so the integration of three Pseudomonas strains had the highest effect on investigated indices in compared with their application lonely. Interaction of bacterium × cultivar (except radiclewet and dried weight and radical length) was significant in all of measured characteristics. Fasih was better than Bahman from the viewpoint of vigor index, germination speed and shoot wet weight